SIMBOL-SIMBOL DALAM NOVEL THE SCARLET LETTER KARYA NATHANIEL HAWTHORNE - RATO NONO, EUNIKE DESTIBELA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACT This study aims at analyzing symbols in the novel The Scarlet Letter by Nathaniel Hawthorne. The writer chooses this topic because symbol is something that means more than it is; therefore symbol is very interesting to be analyzed. The writer uses descriptive method, which describes symbol from literary point of view. The approach used is intrinsic approach. Accordingly, it involves some efforts such as collecting data and analyzing it by using the theory from Landy (1972) and Kennedy (1991). This study shows that there are 67 symbols in total in this novel that fulfilled all the 6 kinds of symbols; 23 word symbols, 23 action symbols, 8 object symbols, 6 character symbols, 4 phrase symbols and 3 scene symbols. There are also major symbols, which are The Letter A and Pearl. These symbols have connection between the major characters, who are Hester Prynne, Pearl and Arthur Dimmesdale. The writer hopes that this study can help students in understanding symbols. Â Key words : types of symbols, major symbols, novel The Scarlet Letter